The Perception of Using ELSA Speak Application to Improve Speaking Skills of Informatics Students: - Kumalasari, Cyintia; Fitri Wulandari (Universitas PGRI Yogyakarta, 2025)
The development of technology can be beneficial for both lecturers to support the teaching and students in language learning progress. Artificial Intelligence has gained particular attention in language instruction these days. It served as a useful addition to language instruction, particularly when it came to teaching pronunciation. Informatics students at the Islamic University of Riau had a lack of pronunciation, especially in pronouncing things about computers in English. Because of that reason, the researcher helped them to find a suitable application that could improve their pronunciation ability. The purpose of this study was to explore the way students learn speaking through mobile application use in the Informatics Engineering Department at the Islamic University of Riau and to know their perception of using ELSA Speak as an Automatic Speech Recognition application. Quantitative methods were used to measure the percentage of students’ perceptions after using the ELSA Speak application.